Climate change influences on aviation: A literature review. (June 2020) - Ryley, Tim; Baumeister, Stefan; Coulter, Liese
Abstract: While the aviation sector has long been referenced as contributing to the causes of climate change, the need for aviation to adapt to the consequences of climate change has not been as well researched or considered. The paper is a systematic quantitative literature review on climate change and aviation, which aims to explicate significant issues affecting aviation in a changing climate and to identify the aviation industry responses on climate change and adaptation. There are 46 references involved in the detailed assessment, selected according to variables such as methodology, paper outcomes and industry stakeholder. This emergent aviation and climate change adaptation literature could be broadened to cover more disciplines and approaches, an increased range of aviation stakeholders and go further beyond the larger airport case studies in developed countries. Further practical and policy developments are needed, particularly surrounding adaptation planning in aviation and the social justice implications of associated policies.